Insignificance of administrative misconduct regarding the conflict of interest: acceptability and criteria - Хамходера, Олег Петрович; Хамходера, О. П.; Khamkhodera, Oleh P. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The work is devoted to the study of the problems of acceptability and justification of exemption (due to insignificance) from administrative liability for misconducts related to conflicts of interest. It has been proved the inadmissibility of premature dogmatic-directive restriction of the jurisdiction of its functional legal obligations under Art. 22 on the Code on Administrative Offenses, when the subject of power actually refuses to legally assess the act as «insignificant». It has been established that the exemption from administrative liability for corruption-related misconduct does not destroy the public law mechanism for combating corruption and does not encourage new torts. It is criticized the application by the courts of such criteria of insignificance of administrative misconducts regarding conflict of interests as: lack of intent (negligent form of guilt), absence of victims of the offense, absence of its great public danger, sincere remorse of the person, further (post-tort) settlement of the conflict of interests and administrative responsibility, its positive characteristics, etc. The borrowing of criminal law has opened up a new space of «insignificance» (which turned out to be acceptable in relation to situations for which it was previously strongly denied – recidivism, lack of remorse, etc.).

Робота присвячена дослідженню проблем прийнятності та обґрунтованості звільнення (через малозначність) від адміністративної відповідальності за проступки, пов’язані з конфліктом інтересів. Доведено неприпустимість передчасного догматично-директивного обмеження юрисдикції його функціонально-правових обов'язків за ст. 22 КУпАП, коли суб’єкт владних повноважень фактично відмовляється юридично оцінити діяння як «незначне». Встановлено, що звільнення від адміністративної відповідальності за корупційні правопорушення не руйнує публічно-правовий механізм протидії корупції та не стимулює нових деліктів. Піддається критиці застосування судами таких критеріїв малозначності адміністративних проступків щодо конфлікту інтересів, як: відсутність умислу (необережна форма вини), відсутність потерпілих від правопорушення, відсутність його великої суспільної небезпеки, щире каяття у вчиненні правопорушення. особи, подальше (постделіктне) врегулювання конфлікту інтересів та адміністративної відповідальності, його позитивні характеристики тощо. Запозичення кримінального права відкрило новий простір «нікчемності» (що виявилося прийнятним щодо ситуацій, щодо яких раніше категорично заперечувалося – рецидив, відсутність докорів сумління тощо).
Khamkhodera O. P. Insignificance of administrative misconduct regarding the conflict of interest: acceptability and criteria / O. P. Khamkhodera // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 194-213.
Keywords: exemption from administrative liability; insignificance of administrative misconducts; borrowing of criminal law; звільнення від адміністративної відповідальності; малозначність адміністративних проступків; запозичення кримінального права; Research Subject Categories::LAW/JURISPRUDENCE::Public law::Administrative law